キョクイキ カイヨウ ケンキュウ ニ オケル フクゴウ リョウイキ ケンキュウ リツアン ニ カンスル ケンキュウ ショウシュウカイ ホウコク - 福地, 光男; フクチ, ミツオ; 小達, 恒夫; オダテ, ツネオ; Fukuchi, Mitsuo; Odate, Tsuneo (2001)
P(論文) 「極域海洋研究における複合領域研究立案に関する研究小集会」を, 平成12年11月1日, 国立極地研究所講義室において開催した。参加者は21名であった。始めに, 平成13年度実施予定の第43次南極地域観測隊(以下, JARE-43)による「しらせ」以外の海洋観測を専門に行う観測船(以下, 「専用観測船」)を導入した南極海海洋観測計画についての進捗状況が報告された。JARE-43では, 生物生産と地球温暖化に関わるガス成分の生成過程及び有機物の鉛直輸送過程を明らかにすることを目標とする。観測時期は, 従来の「しらせ」による航海では実施困難であった盛夏で, 観測海域は東経140-150°周辺の南極海である。現在のところ, 「専用観測船」には, JARE-43副隊長1名及び観測隊員3名が乗船し, 「南極地域観測第VI期5か年計画」に関わる観測実施項目を行い, 関連する研究項目として「南極海と地球環境に関する総合的研究」の一部が同行者によって実施される予定である。地球規模の気候変動に果たす南極海の役割を理解するためには「専用観測船」による観測を継続的に行う必要があり, 平成14年度以降の研究実施体制を検討した。その結果, 科学研究費補助金「特定領域研究(B)」を申請することとなり, その準備の最終的打合せが行われた。 A workshop on "Planning of Future Science in the Polar Ocean Study with Cooperation among Study Groups" was held on November 1,2000,at the National Institute of Polar Research with 21 participants. In this workshop, a plan to charter a research vessel other than "Shirase" was introduced and a science plan using the chartered research vessel by 43rd Japanese Antarctic Research Expedition was discussed. This study is going to be conducted in the sea ice area around 140-150°E in mid-summer (February 2002), when biological production becomes active in the Antarctic Ocean. Oceanographic observations using "Shirase" are difficult to conduct in this season since she supports a wide range of summer operations around Syowa Station. The relationships between biological production and greenhouse effect gas production and the vertical transport of organic materials from the surface to deep ocean will be the focus of this study. At this stage, one deputy leader and three members of JARE, and 25-26 other scientists including graduate students and foreign scientists, will participate in the field observations using the chartered vessel. The members of JARE will conduct a project science program of the VI Phase of JARE, while the other participants will do part of the science program "Antarctic Ocean in Earth System". Since further observations for several years after the summer of 2002 will be required to understand the role of the Antarctic Ocean in global climate ...